INDIVIDUAL BEE’S EXPERIENCE ON ITS BEE CURTAIN DURING THREE DIMENSIONAL DEFLECTIONS BEFORE, DURING AND AFTER SHIMMERING WAVE - Waddoup, Dominique; Singh, Madhusudan Man (Ecoprint: An International Journal of Ecology, 2013)
Giant honeybees (Apis dorsata F.) build open nests far off the ground. As a consequence of their open nesting behaviour giant honeybees seem to be an easy target for predators, such as wasps or birds. However, they have evolved several strategies for defence. Shimmering waves are a defence behaviour, which keep predators far off, by showing visual cues. In the occurrence of shimmering, thousands of colony members, predominantly curtain bees, flip their abdomens in a fraction of a second up to 90 degrees in a rhythmic wave. This effect is comparable to human Mexican waves in the football stadiums. This study gives new insights about how individual bees experience during three dimensional deflections on its bee curtain, before during and after a shimmering wave and how they might decide to participate. DOI: http://dx.doi.org/10.3126/eco.v18i0.9393 Ecoprint An International Journal of Ecology Vol. 18, 2011 Page: 8-15 Uploaded date: 12/20/2013